AgriForEst : un jeu pour élaborer des scénarios sur un terroir villageois d’Afrique Centrale - Églantine Fauvelle; Claude Garcia (VertigO)
Companion Modelling (ComMod) is a support method for natural resource management that emerged in response to top-down approaches. Used by practitioners to support stakeholders in conflict resolution, it is also used by researchers to generate with stakeholders’ involvement, knowledge about complex socio-ecological systems (SES). The approach is well suited to the modelling of systems at the heart of which lies the decision making process of human agents. This study shows how Companion Modelling made it possible to create a research and scenario development tool for the exploration of how a pioneer front operates in a dense forest setting in eastern Cameroon. For three years, a ComMod process was conducted with farmers and hunter-gatherers ; it culminated in the co-construction of the AgriForEst model (Agriculture and Forests in East Cameroon), which was then translated into a board and roleplaying game. Gaming with stakeholders other than those involved in the design served as validation. We present here how the participants took ownership of the tool, and in so doing developed their ability to anticipate future states of their system. Finally, we discuss the signification of the results obtained : the knowledge produced is of a demonstrative nature, and not explanatory. A game session shows how women and men change their strategies, and create new norms, in response to changes, change the forest in the process and are changed in return. AgriForEst shows how a landscape is shaped. One has to play it or see it played to realize it.